2006
DOI: 10.1175/mwr3063.1
|View full text |Cite
|
Sign up to set email alerts
|

Dryline on 19 June 2002 during IHOP. Part I: Airborne Doppler and LEANDRE II Analyses of the Thin Line Structure and Convection Initiation

Abstract: The evolution and finescale structure of a dryline that initiated a line of thunderstorms is presented. Both the along-line variability and mean vertical structure were examined using data collected by an airborne Doppler radar and a water vapor differential absorption lidar (DIAL). The initiation of convection appeared to result from the diurnally induced easterly flow in the maritime air east of the dryline that typically develops late in the day. This flow increased the low-level convergence and allowed ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
70
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(81 citation statements)
references
References 60 publications
11
70
0
Order By: Relevance
“…Summer has a decreased likelihood of migration activity (i.e., more random flight directions of biota are more likely), thus it is possible our summer results here are more robust. The increase in mean horizontal wind speed observed above the surface layer during the transition may play a role in enhancing existing horizontal wind convergence, as found along boundaries such as drylines, and could promote the invigoration of convective elements, similar to that shown by Jones and Bannon (2002) and Murphey et al (2006).…”
Section: Horizontal Wind Speed and Convergencementioning
confidence: 68%
See 3 more Smart Citations
“…Summer has a decreased likelihood of migration activity (i.e., more random flight directions of biota are more likely), thus it is possible our summer results here are more robust. The increase in mean horizontal wind speed observed above the surface layer during the transition may play a role in enhancing existing horizontal wind convergence, as found along boundaries such as drylines, and could promote the invigoration of convective elements, similar to that shown by Jones and Bannon (2002) and Murphey et al (2006).…”
Section: Horizontal Wind Speed and Convergencementioning
confidence: 68%
“…Still, in the mean a steady convergence increase from −0.85 × 10 −3 s −1 at 3 h before sunset to + 0.69 × 10 −3 s −1 at 2 h after sunset occurs and is statistically significant at the 0.01 probability value. This signature may relate to an increase in pre-existing low-level convergence along drylines shown by Jones and Bannon (2002) and could act in specific circumstances to aid in convective initiation or enhancement, akin to the Murphey et al (2006) case study.…”
Section: Horizontal Wind Speed and Convergencementioning
confidence: 94%
See 2 more Smart Citations
“…Many studies have demonstrated that misocyclones along air mass boundaries distort the boundaries and produce local maxima of low-level convergence and vertical velocity in their vicinity, which often could be preferred regions to form clouds and/or radar reflectivity cores (e.g., Wilson et al 1992;Atkins et al 1995;Lee and Wilhelmson 1997b;Friedrich et al 2005;Arnott et al 2006;Murphey et al 2006;Marquis et al 2007;Wakimoto and Murphey 2009). Although well-defined vortices with quasi-circular vorticity contours do not develop in the present simulations, it is suggested that in the U15-S2 and U20-S2 cases the concentrated vertical vorticity distorted the horizontal wind field and enhanced the low-level convergence in the vicinity of the vorticity maxima, leading to formation of the precipitation maxima north of the bow apexes.…”
Section: ) Stably Stratified Casesmentioning
confidence: 99%